QQuake, a QGIS Plugin for Loading Seismological Data From Web Services - Locati, Mario; Vallone, Roberto; Ghetta, Matteo; Dawson, Nyall (Frontiers in Earth Science, 2021)
An increasing number of web services providing convenient access to seismological data are becoming available in recent years. A huge effort at multiple levels was required to achieve this goal and the seismological community was engaged in the standardisation process of both data formats and web services. Even if the access to seismological data is much easier than in the past, the average user encounters problems because of the large number of web services, and due to the complexity of the discipline-specific data encodings. In addition, most seismological web services did not widely adopt cross-disciplinary standards such as those by the Open Geospatial Consortium (OGC), and established their own standards instead, primarily those by the International Federation of Digital Seismograph Networks (FDSN). This article introduces “QQuake”, a plugin for QGIS - the open source Geographic Information System - that aims at making access to seismological data easier. The plugin is based on Open Source code available on GitHub, and it is designed in a modular and customizable way, allowing users to easily include new web services.